Genomic and metagenomic analysis of microbes in a soil environment affected by the 2011 Great East Japan Earthquake tsunami - Hiraoka, Satoshi (BMC Genomics, 2016)
BACKGROUND: The Great East Japan Earthquake of 2011 triggered large tsunami waves, which flooded broad areas of land along the Pacific coast of eastern Japan and changed the soil environment drastically. However, the microbial characteristics of tsunami-affected soil at the genomic level remain largely unknown. In this study, we isolated microbes from a soil sample using general low-nutrient and seawater-based media to investigate microbial characteristics in tsunami-affected soil. RESULTS: As expected, a greater proportion of strains isolated from the tsunami-affected soil than the unaffected soil grew in the seawater-based medium. Cultivable strains in both the general low-nutrient and seawater-based media were distributed in the genus Arthrobacter. Most importantly, whole-genome sequencing of four of the isolated Arthrobacter strains revealed independent losses of siderophore-synthesis genes from their genomes. Siderophores are low-molecular-weight, iron-chelating compounds that are secreted for iron uptake; thus, the loss of siderophore-synthesis genes indicates that these strains have adapted to environments with high-iron concentrations. Indeed, chemical analysis confirmed the investigated soil samples to be rich in iron, and culture experiments confirmed weak cultivability of some of these strains in iron-limited media. Furthermore, metagenomic analyses demonstrated over-representation of denitrification-related genes in the tsunami-affected soil sample, as well as the presence of pathogenic and marine-living genera and genes related to salt-tolerance. CONCLUSIONS: Collectively, the present results would provide an example of microbial characteristics of soil disturbed by the tsunami, which may give an insight into microbial adaptation to drastic environmental changes. Further analyses on microbial ecology after a tsunami are envisioned to develop a deeper understanding of the recovery processes of terrestrial microbial ecosystems. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2380-4) contains supplementary material, which is available to authorized users.